Deleterious effects of Pfaffia glomerata (Spreng.) Pedersen hydroalcoholic extract on the seminiferous epithelium of adult Balb/c mice. Issue 5 (1st September 2020) - Matta, Ana Paula L. F.; Leite, João Paulo V.; Gomes, Marcos L. M.; Morais, Danielle B.; Carvalho, Fabíola A. R.; Otoni, Wagner C.; Matta, Sérgio L. P.
Abstract: Several plant species such as Pfaffia glomerata are widely used in traditional Brazilian medicine as stimulants and aphrodisiacs. In this regard, the aim of our study was to explore the effects of the long‐term intake of the hydro‐alcoholic root extract of P glomerata on the germ and somatic cells within the seminiferous tubules in adult Balb/c mice. The experimental groups were placed as: controls (water and DMSO), and treated with 300 and 400 mg/kg of the root extract. The number of germ and somatic cells, the proportion of pathological seminiferous tubules, and the germ cell apoptotic levels were evaluated. The volume and proportion of the seminiferous epithelium was decreased after the extract intake due to the increased germ cell apoptotic levels. Vacuolization of Sertoli cell cytoplasm was observed widely in pathological tubules, along with fully disorganized epithelia, showing multinucleated cells, which lead to decreased daily sperm production. Taken together, our results indicate that long‐term intake of the P glomerata caused deleterious effects on spermatogenesis by inducing apoptosis and altering the seminiferous tubule's epithelial dynamics.